2022
DOI: 10.14218/jcth.2022.00177
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Intrahepatic cccDNA and Integration of HBV in Chronic Hepatitis B Patients with a Functional Cure

et al.

Abstract: Background and Aims: Functional cure (FC) is characterized by the clearance of the hepatitis B surface antigen from the serum of patients with chronic hepatitis B (CHB). However, the level of intrahepatic covalently closed circular DNA (cccDNA) and hepatitis B virus (HBV) integration remains unclear. We conducted this study to determine them and reveal their value in the treatment of CHB. Methods: There were two sessions to elucidate the changes in intrahepatic cccDNA and HBV integration after antiviral therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Our prior studies reported that the levels of intrahepatic covalently closed circular DNA (cccDNA) are associated with HBV relapse. 3 Positive serum HBV RNA and high level of hepatitis B core-related antigen (HBcrAg) at the end of treatment, reflect active transcription from cccDNA and are potential predictors of HBsAg reversion in patients with functional cure after interferon-based therapy. 4,5 In addition to viral replication factors, lasting cellular and humoral immune responses to HBV are vital for sustaining a loss of serum hepatitis B surface antigen (HBsAg).…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…Our prior studies reported that the levels of intrahepatic covalently closed circular DNA (cccDNA) are associated with HBV relapse. 3 Positive serum HBV RNA and high level of hepatitis B core-related antigen (HBcrAg) at the end of treatment, reflect active transcription from cccDNA and are potential predictors of HBsAg reversion in patients with functional cure after interferon-based therapy. 4,5 In addition to viral replication factors, lasting cellular and humoral immune responses to HBV are vital for sustaining a loss of serum hepatitis B surface antigen (HBsAg).…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…Although, more than 20% of patients who achieved functional cure following interferon‐based therapy may experience hepatitis B virus (HBV) relapse, the mechanisms causing the relapse are not fully understood 6 . Our previous research linked virological relapse to the high level of intrahepatic covalently closed circular DNA (cccDNA), but we also discovered the limitations of cccDNA in predicting virological relapse, as it could only explain the virological relapse in some patients 7 …”
Section: Introductionmentioning
confidence: 97%
“…Up to now, no studies have reported whether the transcription of intrahepatic HBV is indeed completely silenced in patients who have achieved functional cure via pegylated‐interferon (PEG‐IFN)‐based therapy. Furthermore, our previous results showed that intrahepatic HBsAg remains positive in patients with PEG‐IFN‐induced HBsAg seroclearance 7 . This suggests that intrahepatic HBV RNA is still being transcribed in these patients, but it is unclear whether it originates from cccDNA or integrated HBV DNA.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations